Maharah dalam Koleksi Naskah Kuno - Azani, Azzahra Nur (Tarbiya Islamica, 2024)
This purpuse of this research to see the effectiveness of digital learning media used as a learning outcome for students of Arabic Language Education Study Program (PBA) UIN Imam Bonjol Padang. This research analyzes how digital media affects students' motivation to understand the learning of maharah in Arabic. The research method uses qualitative analysis, the data collection techniques used are questionnaires, classroom observations, and in-depth interviews with student of PBA Study Program (PRODI) students. Based on the data obtained, it was found that digital media plays an important role in the technological era in learning maharah. The results generated are very large as a result of learning maharah of PBA PRODI students at UIN Imam Bonjol Padang by using various digital media and must be in accordance with the learning context. It is concluded that the application of digital media for Arabic language learning, especially maharah learning, is very effective in arousing students' learning motivation in understanding and learning Arabic.